2003
DOI: 10.1128/jcm.41.3.1252-1255.2003
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sample Preparation Method for Safe and Rapid Detection of Bacillus anthracis Spores in Environmental Powders and Nasal Swabs

Abstract: Bacillus anthracis spores have been used as a biological weapon in the United States. We wanted to develop a safe, rapid method of sample preparation that provided safe DNA for the detection of spores in environmental and clinical specimens. Our method reproducibly detects B. anthracis in samples containing <10 spores.Bacillus anthracis spores, a recent threat, can remain dormant for years while retaining full virulence (5,10,13,20,21,22; S. Endicott, E. Hagerman, and M. Furmanski, Letter, JAMA 284:561-562, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 20 publications
0
41
0
3
Order By: Relevance
“…Total DNA was extracted from the original environmental specimens and used as template in a PCR assay for Ba813, an intergenic chromosomal marker for B. anthracis, as previously described (19,22). In addition, the PCR assays for the pX01 and pX02 plasmids and chromosomal marker were repeated following LRN procedures (31).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total DNA was extracted from the original environmental specimens and used as template in a PCR assay for Ba813, an intergenic chromosomal marker for B. anthracis, as previously described (19,22). In addition, the PCR assays for the pX01 and pX02 plasmids and chromosomal marker were repeated following LRN procedures (31).…”
Section: Methodsmentioning
confidence: 99%
“…After more tests demonstrated that none of these were B. anthracis, the 19 isolates were given to the Center for Biological Defense for further examination. By in-house real-time PCR assays, 14 of the 19 isolates and respective powders tested positive only for the Ba813 chromosomal element, which is considered to be unique to B. anthracis (19,22,23). These were not studied further.…”
mentioning
confidence: 99%
“…30 These genetic markers provide limited specificity and require additional timeconsuming and labor-intensive post-PCR analysis steps. Other areas of the chromosome have also been investigated as potential DNA-targets for identification purposes, including the so-called BA813 [31][32][33][34][35][36][37][38] and BA5510 sequences, 19 genes bclB, 39 sap, 40,41 saspB, 5,42 and sspE, 22,43 the B-type small acid-soluble spore protein gene (SASP), 44 a glycosyltransferase group 1 family protein, 45 a protein showing similarities with an abhydrolase, 18 and several DNA loci located on prophage regions, 17 i.e., BA5345, 21 BA5357, 46 and PL3. 47 Although most of these regions have been claimed to be anthrax-specific, B. cereus strains sometimes yield false positive results.…”
Section: Literature Survey Of Pcr-based Detection Methodsmentioning
confidence: 99%
“…Assays mentioned by the World Health Organization (WHO) 31,40,44 were also included in the ring trial, as well as a hydrolysis probe assay 35 that targets the often used BA813 marker [31][32][33][34][35][36][37][38] (Table 3). The latter marker has shown in silico cross-reactions toward the near-neighbor strains in use in this trial and was included for this reason.…”
Section: Ring Trialmentioning
confidence: 99%
“…When areas contain numbers of spores lower than the test assay detection limit, the resulting false-negative findings may lead first responders to employ relaxed safety precautions. Although the assays tested are selfcontained and easy to use in the field, their sensitivity fails to meet that of our laboratory experiments (e.g., Ͻ10 spores on environmental swab samples) (2).…”
mentioning
confidence: 99%